The effects of an acute resistance exercise bout on Insulin like growth factor-I and 3 binding proteins in well-trained men and women - Hatfield, D. L.; Kraemer, W. J.; Vingren, J. L.; Anderson, J. M.; Volek, J. S.; Nindl, B. C.; Thomas, G. A.; Ho, J. Y.; Fragala, M. S.; Maresh, C. M. (The Journal of Strength and Conditioning Research, 2010)
Insulin-Like Growth Factor I (IGF-I), known to mediate many of the growth and repair processes of skeletal muscle in response to long term resistance training, is acutely and chronically regulated by its family of six binding proteins (BPs). In contrast to the circulating concentrations of IGF-I, the IGFBP's show a more consistent response to an acute bout of resistance exercise, despite receiving less attention in the literature than circulating IGF-I. Furthermore, gender differences in the responses of the IGFBPs to resistance exercise have not been examined. Thus, the primary purpose of this investigation was to assess the response of IGF-I and three IGFBPs (IGFBP-1, -2, and -3) to an acute resistance exercise bout in well-trained men and women. Eight men (BM: 87.0 +/- 18.5 kg; Ht: 175.3 +/- 6.7 cm; Age: 21 +/- 1 yrs) and seven women (BM: 76.4 +/- 8.8 kg; Ht: 164.6 +/- 6.7 cm; Age: 24 +/- 5 yrs) volunteered to participate in this study. Each subject performed an acute resistance exercise bout and blood was collected pre-, immediately post- (IP), and 70 minutes ( + 70) post-exercise. Women had significantly (p <= 0.05) higher concentrations of IGF-I and IGFBP-3 at rest and IP, although exercise-induced increases in circulating IGF-I were observed in both genders. Significant (p <= 0.05) exercise-induced increases were observed for IGFBP-1 in the women at IP and + 70 and at + 70 in the men, and for IGFBP-2 at IP in both genders. The results from this study demonstrate the dynamic nature of IGF-I and its family of BPs and illustrate potential gender differences in the regulation of IGF-I bioavailability surrounding an acute bout of resistance exercise. Since the IGFBPs are greatly affected by nutrition, training, and gender, a better understanding of the dynamics of the IGF-I family surrounding a resistance training bout may be used to prescribe dietary and training regimes in order to optimize their response.